Candida albicans modulates murine and human Beta Defensin-1 during vaginitis - Miró, María Soledad (2021)
Vulvovaginal candidiasis (VVC) and recurrent vulvovaginal candidiasis (RVVC) are two forms of a disease caused by Candida spp. β-defensin (BD) is one of the most important families of antimicrobial peptides in the female genital tract and includes molecules that exert essential local functions as antimicrobial and PMN chemoattractant peptides. However, the information on their role during murine and human VVC and RVVC is limited. Thus, we analyzed the behavior and contribution of BD1 to the local response in a VVC mice model and the local cytokine profile and human BD1 and BD3 expression in cervicovaginal lavage from patients with VVC and RVVC. We demonstrated that, in patients with RVVC BD1, mRNA and protein expression were severely diminished and that the aspartate proteinase and lipase secreted by C. albicans are involved in that decrease. This study provides novel information about the pathogenesis of VVC and describes a highly efficient C. albicans escape strategy for perpetuating the infection; these results may contribute to the development of new or combined treatment approaches.